Para-substituted sulfonic acid-doped protonated emeraldine salt nanobuds: a potent neural interface targeting PC12 cell interactions and promotes neuronal cell differentiation. (7th January 2021) - Shrestha, Sita; Shrestha, Bishnu Kumar; Joong, Oh Kwang; Park, Chan Hee; Kim, Cheol Sang
Abstract : Surface functionalized protonated emeraldine salt (PES) synthesized at 0.18 V provide robust electrically conductive system with low surface resistivity (81.18 mΩ). The PES show ability of cell-type specific microenvironment supporting PC12 cells for neural differentiation. Abstract : Structural parameters, such as metal-like semiconductor and electrochemical properties of functionalized polyaniline, hold great potential especially for the development of the cell–substrate interface due to its ion/electron transfer ability. We report the one-step synthesis of sulfonic acid-doped polyaniline nanobuds (s-PANINbs) with controlled shape/size under various oxidation potentials. The different oxidation states of s-PANINbs are used to investigate the cell-specific platform for the induction of neuronal networks in PC12 cells, including the growth, proliferation, and differentiation of cells. The unique structure of one-dimensional (1-D) s-PANINbs enhances its intrinsic conductive properties, and facilitates the dispersibility and electrochemical activity via covalent bonding with dopants. The protonated emeraldine salt nanobuds of s-PANINbs synthesized at 0.18 V anodic potential demonstrated low resistivity (∼81.18 mΩ) and charge transfer resistance (∼3253 Ω). The most biologically compatible protonated emeraldine salt was used in vitro to induce PC12 cells associated with neurite outgrowth, contributing to the electrophysiology of neuronal cells under an external electrical stimulation. The western blotting analysis and qRT-PCR results show that β-III Tubulin, synapsin I, and TREK-1 are highly expressed in PC12 cells, confirming their successful differentiation into neural-specific cells. Our approach demonstrates the promising role of the self-standing framework based on the s-PANINbs of the protonated emeraldine salt in peripheral nerve repair for the future in vivo cell-interface.